Organizational Culture, Human Resource Strategies, and Organizational Climate as Modifiers of Organizational Performance of Region Ii Trauma and Medical Center - Arizala Dalapo, Irene (Indonesian Association for Public Administration, 2025)
This study aimed to analyze organizational culture, HR strategies, organizational climate, and performance at Region II Trauma and Medical Center (R2TMC) and their relationships. A descriptive-inferential research method using a structured questionnaire was employed, with 314 randomly selected personnel as respondents. Data were analyzed through descriptive statistics and correlation procedures. Findings revealed a strong organizational culture marked by employee involvement, consistency, adaptability, and a shared mission. HR strategies were effectively implemented in recruitment, performance management, and employee development. The organizational climate scored high in clarity, standards, responsibility, and teamwork, while R2TMC demonstrated strong performance in ethics, leadership, and communication. The study confirmed significant correlations between these factors. A strong organizational culture enhances HR strategies and climate, while effective HR strategies foster a positive climate. Aligning these elements is crucial for maximizing performance. Results suggest R2TMC’s responsive approach supports staff growth and well-being, impacting financial, operational, and employee management outcomes. Finally, the study proposes a performance enhancement model based on these findings.